Topical nepafenac in the treatment of diabetic macular edema - David Callanan (Dove Medical Press, 2008)
David Callanan, Patrick WilliamsTexas Retina Associates, Arlington, TX, USAPurpose: To determine the safety and efficacy of topical nepafenac 0.1% in the treatment of diabetic macular edema.Methods: A consecutive case series was performed of patients treated with nepafenac monotherapy twice daily for diabetic macular edema. Visual acuities (VA) at baseline and final visit were recorded. Foveal thickness, based on optical coherence tomography, was also recorded.Results: Six eyes of 5 patients were included in this study. Median initial Snellen vision was 20/100 (range, 20/40–20/400). After a mean of 210 days (range, 182–259), median final VA was 20/75 (range, 20/40–20/400). Four eyes gained vision and two eyes maintained vision. Mean pre-treatment vision was 0.78 logMAR and final VA was 0.67 logMAR, for a statistically significant improvement (p < 0.05). Mean initial foveal thickness was 417 microns (range, 286–599). After a mean of 178 days (range, 91–259), mean foveal thickness was 267 microns (range, 158–423), showing a statistically significant improvement (p < 0.05). Each eye had an improvement in foveal thickness.Conclusion: The results from these 6 eyes suggest that nepafenac 0.1% may have activity against diabetic macular edema and warrants further investigation.Keywords: diabetes, diabetic macular edema, inflammation, macular edema, nepafenac, NSAIDs